Analysis of customers' electricity consumption behavior for peak load shifting - Bingxin WANG; Yan HOU; Hongwang FANG; Yuze CHEN; Jian LIU (Dianxin kexue)
In order to implement well-directed peak load shifting for massive customers,a method for analyzing massive customers' electricity consumption behavior for peak load shifting was proposed.Firstly,clustering algorithm was used to cluster daily load curves of the main power grid in the previous year and get load characteristics in different dates.Then the load curves of all customers under every date cluster were clustered,the peak load shifting method was derived by comparing the load characteristics of the main power grid and customers.Finally,the peak load shifting method in a future day was given by date matching between the future day with a historical day using dynamic time warping (DTW).Empirical study shows that the method is conductive to peak-valley electricity pricing and orderly electricity consump-tion and can further achieve peak load shifting and stable operation of the main power grid.